Some properties of positive derivations on f-rings II - Redfield, R. H. (International Journal of Advanced Mathematical Sciences, 2014)
A counterexample is provided to show that Theorem 10(b)(i)  in the article “Some properties of positive derivations on f-rings” by Henriksen and Smith is false. Correct proofs are given for some results in the paper that use Theorem 10(b)(i) in their proofs. Keywords: lattice-ordered ring, f-ring, positive derivation, polynomial ring.